Diet quality based on Healthy Eating Index for Malaysians (M-HEI) among IIUM Kuantan students - Ayob, Rosnani; Mohd Shukri, Nor Azwani (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2020)
Introduction: Previous studies showed that there has been an increasing number of university students who experience malnutrition. This situation is worrying as they may develop nutritional problems and be risky to get non-communicable diseases in the future. Thus, this cross-sectional study aimed to assess the diet quality and its association with nutrition knowledge among health sciences and non-health sciences students at the International Islamic University Malaysia (IIUM) Kuantan Campus. Methods: A total of 180 students from health sciences and non-health sciences programs was conveniently recruited into this study. They were requested to complete a questionnaire which consisted of sections on the Healthy Eating Index for Malaysians (M-HEI) and nutrition knowledge. The MHEI contains nine food groups, each has a score ranging from 0 to 10. The total score was divided by the maximum score and changed to a percentage value. The score which is less than 51% indicates poor diet quality, 51 % until 80% shows moderate diet quality and more than 80% indicate a good diet quality. The nutrition knowledge section contained questions with True/False/Do Not Know answer options. Statements answered correctly were given a score of one whereas statements answered incorrectly or with the ‘Do Not Know’ option were scored as zero. Results: The diet quality of the health sciences students was higher than the non-health sciences students (mean±SD M-HEI scores 56.9±10.2 vs 51.7±9.2, p=0.025). Their nutrition knowledge mean score was also higher than their non-health sciences counterparts (19.9±3.8 vs 17.3±4.2, p<0.001). In addition, the nutrition knowledge score was found to be positively correlated with the M-HEI score (p=0.035). Conclusion: The health sciences students have better nutrition knowledge, and this may contribute to better diet quality than their non-health sciences counterparts.